Diversity and Stratigraphic Distribution of Sphenophytes in the Permian of the Paraná Basin, Brazil - Neregato, Rodrigo; Boardman, Daiana Rockenbach [UNESP]; Rohn, Rosemarie; Iannuzzi, Roberto (My University, 2024)
Sphenophytes have been recognized in the Brazilian Paraná Basin since the early twentieth century. The group is recorded from the late Pennsylvanian to Permian in deposits of the Itararé Group and Rio Bonito, Teresina and Rio do Rasto formations. The most frequent genera are Paracalamites, Phyllotheca, Sphenophyllum, and Schizoneura. Together with important reproductive structures and other vegetative parts, these genera assist the reconstruction of past floristic scenarios as well in the biostratigraphic correlations between their deposits with other regions of Gondwana. The first appearances of Sphenophyta in the basin are recorded in the Pennsylvanian Pre-Glossopteris Flora from the Itararé Group represented by Paracalamites australis and the forms related to the genus Sphenophyllum. This floral record occurred during interglacial and periglacial periods under the cooling regime of the Late Paleozoic Ice Age, a climatic event that spanned all over Gondwana. The highest diversity of Sphenophytes is assigned from the Asselian to middle Artinskian, which comprises the uppermost portion of the Itararé Group and Rio Bonito Formation. Phyllotheca, Stephanophyllites, and Annularia appear in association with reproductive structures like Giridia, Paragiridia, and Notocalamites. In this interval, there occurred the broad domain of Glossopteris corresponding to the typical “Glossopetris Flora” in the post-glacial environmental condition. The Guadalupian–lower Lopingian, particularly the Rio do Rasto Formation, records the impoverishment and final disappearance of the Glossopteris Flora in the basin under warm and predominantly semiarid conditions, still with a relative abundance of small stems of Paracalamites spp., but few fragmentary occurrences of Sphenophyllum paranaense, Sphenophyllum cf. S. thoni, Schizoneura gondwanensis, and not yet studied strobiles.